The Existence of Time - Gray Hansen Limantoro; Riski Zulkarnain; Muhammad Ahsin Rifa'i; Yusuf Wibisono (CV Projurnal Mitra Publikasi, 2025)
The concept of time has been the subject of much debate in philosophy, physics and cognitive science. Some theories hold that time is a fundamental entity in the structure of the universe, while others argue that time is merely a human mental construct. This research examines the existence of time from various perspectives, including the theory of relativity, the philosophies of idealism and materialism, and the theory of causality. The study shows that time cannot be separated from space, as expressed in the concept of space-time. In addition, time also has probabilistic characteristics, where future events are affected by the past and current conditions. The purpose of this research is to find out about the concept and implementation of time. The information is extracted using the desk research method, in accordance with the study with the discussion of three main theories of time: Presentism, Eternalism, and Growing Block Theory. The results show that Causality Time is more in line with the idea that time is already present by the various probabilities of events occurring, where the past and present are real, while the future is real with the chance of events stemming from causality. Thus, time is not just a measure of change, but also a fundamental element that shapes reality and influences causal relationships in the universe.